(3eYOf GddBdi aj GdCSGfjO GdYhGdis - (3CHh GdeMGSf eMeO Hf Ndjd Hf EHQGgje GdbGhbMj,J (B1305 (3g` s ((3MSf Hf YHO Gddg GdYQOGJi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi hUd ef EfbWY Edjg HUMjM GdJbhi CeG HYO ajbhd deG cGf Yde GdMOjK ef CTQa GdYdhe ai GdbOje hGdMOjK PcQJ LedI ef GdCSGfjO GdYdjI eJUdI dCQHYjf cJGHkG ef CTgQ GdcJH GdMOjKjI s
(3BNQgG (B:s
(3Yf eYGP Hf LHd bGd (B: (3BNQ cdeI aGQbJ YdjgG QShd Gddg (B( (3U(B) (3Cf bdJ jG QShd Gddg CNHQfi HCMH GdCYeGd Edi Gddg bGd Cf JehJ hdSGfc QWH ef PcQ Gddg hgPG BNQ eG CQOfGg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hGdahGJM hGdahGUd HGdMeQI hGdRQbI hGdUaQIs
(3HBNQgG ELGRI ef GdeDda dChdGOg s
(3HBNQgG Jedc HGSe hdO CHj Gdfgi eMeO s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs